Snake Cathelicidin Derived Peptide Inhibits Zika Virus Infection - Xing, Meichen; Ji, Mengyao; Hu, Jingmei; Zhu, Tengyu; Chen, Yaoyao; Bai, Xuewei; Mwangi, James; Mo, Guoxiang; Lai, Ren; Jin, Lin (Frontiers in Microbiology, 2020)
Zika virus (ZIKV) is a mosquito-borne virus belonging to the genus Flavivirus and has reemerged in recent years with epidemic potential. ZIKV infection may results in severe syndromes such as neurological complications and microcephaly in newborns. Therefore, ZIKV has become a global public health threat and currently there is no approved specific drug for its treatment. Animal venoms are important resources of novel drugs. Cathelicidin-BF (BF-30) is a defensive peptide identified from Bungarus fasciatus snake venom and has been shown to be an excellent template for applicable peptide design. In this study, we found that ZY13, one of the peptidic analogs of BF-30, inhibits ZIKV infection in vitro and in vivo. Mechanistic studies revealed that ZY13 can directly inactivate ZIKV and reduce the production of infectious virions. Further studies also indicated that administration of ZY13 strengthen the host antiviral immunity via AXL-SOCS (suppressor of cytokine signaling protein) pathway. Additionally, the results of mouse experiment suggest that ZY13 efficiently restrict ZIKV infection and improve the growth defects of ZIKV-infected mouse pups. Together, our findings not only demonstrate that ZY13 might be a candidate for anti-ZIKV drug, but also indicated the importance of animal venom peptides as templates for antivirals development.